Measurement of liquid film flow on inclined wall using photochromic dye marking method - Nurrina, Rosli (2011)
The objective of present work is to apply a liquid film measurement technique, which is called as photochromic dye marking method. This technique utilizes a color change of the photochromic dye contained in the test film when ultraviolet (UV) light from Nd: YAG laser (X 355 nm) is irradiated. The movement of the dye trace formed by the UV irradiation is then captured by a high speed video camera and analyzed to obtain the surface velocity. The movement of wave passing by the dye trace is also analyzed and comparison between them is made to investigate the velocity change. The data regarding such information is nowadays lacking. Apart from the measurement as mentioned above, this paper also aimed to produce the average waves velocity and film thickness results data. The wave velocity is measured by cross correlating two signals of light intensity from two laser beams spaced in a known distance; parallel with the film flow direction. Taking advantages from one of the laser beams sourced from a diode laser light (X= 407 nm), the thickness is determined based on the intensity of absorption light passing through the test film contained a fluorescent dye, coumarin-153. This technique is a non-intrusive and easy technique to be conducted, as it only requires simple optical arrangement and calibration process. The data from this study are also compared with previous published results [1],.[18], [19]. The experiment is conducted at different inclination angle from the horizontal direction (0= 300 , 60°, 90°). The 'effects of Reynolds number (Re= 50.8, 81.3, 108.4, 138.9) and film flow characteristics at various positions on the inclined wall defined as distance from liquid inlet (x= 60 mm, 100 mm, 140 mm, 180 mm) are investigated.